Frailty, multimorbidity and functional status as predictors for health outcomes of acute psychiatric hospitalisation in older adults. (2nd January 2020) - Benraad, Carolien E. M.; Disselhorst, Luc; Laurenssen, Nicky C. W.; Hilderink, Peter H.; Melis, René J. F.; Spijker, Jan; Olde Rikkert, Marcel G. M.
Abstract: Objectives: Frailty, multimorbidity and functional decline predict adverse health outcomes in community dwelling older people and older patients in general hospitals. This study investigates whether these characteristics separately are independent predictors of health outcomes of acute psychiatric hospitalization. Methods: Observational study in a prospectively sampled cohort of older patients, consecutively admitted to a psychiatric hospital. On admission we assessed frailty (Frailty Index and walking speed); multimorbidity (Cumulative Index Rating Scale Geriatrics (CIRS-G)) and functional status (Barthel Index). We used the Clinical Global Impressions of Improvement scale (CGI-I) as the psychiatric outcome measure, and dichotomized discharge destination as overall outcome measure: favourable (able to return home or previous care level) or adverse (death, or move to higher level of residential care). Results: We included 120 patients, 74.6 years (±7.8). 52.5% of the patients was frail (FI ≥0.25). The mean level of the CIRS-G was 13.5 (5.4). Mean CGI-I at discharge was 2.8 (± 1.0), indicating moderate improvement in the psychiatric outcome. Neither FI, CIRS-G, nor Barthel scores were, independent of age, sex and diagnosis, associated with the CGI-I. FI was predictive for adverse discharge destination (OR 1.91, 95%CI 1.09–3.37 per 0.1), as were higher CIRS-G (OR 1.19 95%CI 1.06–1.34, per point) and lower walking speed (OR 1.35 95%CI 1.06–1.72 per 0.1 m/s). Conclusions: Half of our patients were frail and had a high level of multimorbidity. The FI, walking speed and multimorbidity did not predict improvement of psychiatric symptoms at discharge, but independently helped to predict adverse discharge destination.